Implementation of Poor Family Assistance Policy in Sidotopo Village, Surabaya City - Ryski Bin Isnaini; Ertien Rining Nawangsari (Publik : (Jurnal Ilmu Administrasi), 2023)
The policy regarding assistance to poor families has made the poverty rate in the city of Surabaya, which was originally one million people, drop drastically to just two thousand people. This policy is considered to eliminate the rights of residents who need assistance, so that many less fortunate residents are not recorded as poor families and the facts on the ground are that there are still many residents who can afford this assistance. The purpose of this study was to determine the successful implementation of the Assistance Policy for Poor Families in the Sidotopo Village, Surabaya City. This research uses qualitative methods, namely by observation, interviews, or document review. The type of research chosen is descriptive research. The results of research findings in the field show that the implementation of the Poor Family Assistance Policy in Sidotopo District, Surabaya City, in general, from several indicators such as policy targets and standards, social environment and economic environment and the disposition used shows that the category has not been successful. As for the resource category, the quality of relationships between organizations, and the characteristics of implementing institutions/organizations.